Use and exchange of genetic resources in molluscan aquaculture - Ximing Guo (Blackwell Publishing Asia Pty Ltd, 2025)
Molluscs are major aquaculture species worldwide. Molluscan aquaculture accounts for approximately 27% of the total world aquaculture production. The use and exchange of genetic resources have played an important role in the development of molluscan aquaculture. The introduction and use of nonnative species have been instrumental in oyster and scallop aquaculture; for example, the Pacific oyster, translocated from Japan, supports major aquaculture industries in many countries of North and South America, Europe, Asia and Africa. Bay scallops introduced from the USA account for an annual production of over 600 000 t in China. Non-native genetic materials have also been used for the genetic improvement of native species through interspecific and intraspecific hybridization. Unique genetic lines, such as disease-resistant strains, have been developed through selective breeding in some molluscs, although significantly more efforts are needed. Although the importance of genetic resources is apparent, the identification, protection and utilization of molluscan genetic resources remain a challenge.